Pengaruh Lingkungan Kerja dan Promosi Jabatan Terhadap Kinerja Karyawan di Pt Karuniatama Polypack - Ernita Dwi Lestari; Muhamad Azis Firdaus; Dewi Megawati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Employee performance plays a crucial role in supporting organizational effectiveness and achieving company objectives. However, employee performance can be influenced by various factors, including work environment conditions and job promotion opportunities. This study aims to analyze the effect of work environment and job promotion on employee performance at PT Karuniatama Polypack, both partially and simultaneously. The research employed a quantitative approach with an associative research method. The population consisted of employees of PT Karuniatama Polypack, with 103 respondents selected as the research sample. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The findings reveal that the work environment has a positive and significant effect on employee performance. Job promotion also has a positive and significant effect on employee performance. Furthermore, the results indicate that work environment and job promotion simultaneously have a positive and significant effect on employee performance. These findings suggest that creating a supportive work environment and implementing a fair and transparent job promotion system can improve employee motivation, productivity, and overall performance. Therefore, management should continuously enhance both factors to support organizational goals and improve company competitiveness.